Determinan Kegagalan Pemberian ASI Eksklusif Pada Ibu Bekerja: A Literature Review - Isne Susanti; Yulia Vanda Editia; Mahardika Primadani (Jurnal Medika Nusantara, 2024)
Mother's breast milk is the best food for babies because it is able to meet children's nutritional needs during 0-6 months. One of the problems with exclusive breastfeeding is that breast milk production. This was an impact on achieving exclusive breastfeeding coverage, based on UNICEF data, exclusive breastfeeding coverage in Indonesia is around 50.7% for children under five aged 0-6 months. Breast milk has many benefits for babies and mothers, some of which are breast milk containing various complete nutrients for babies, strengthening and establishing love between mother and baby, reducing the risk of bleeding and speeding up the recovery of the mother's health. Based on this background, it is necessary to carry out research which aims to examine and determine the factors that determine the failure of providing exclusive breastfeeding to working mothers. The method used in this research is a critical review of complete texts in Indonesian. Articles were selected in stages using the Preferred Reporting Items for Systematic Review and Meta Analysis (PRISMA) assessment tool, then duplicate filtering was carried out, screening was carried out based on title and abstract, full text, feasibility study and until the final stage 8 articles were found that met the inclusion criteria and feasibility study. The results of research based on 8 selected articles found that the determining factors for the failure of exclusive breastfeeding for working mothers were the level of education, knowledge and attitudes. Factors that may occur are insufficient working hours and breast milk production. The strengthening factor is support from superiors, family and health workers